BURN-OUT DU SOIGNANT AUX URGENCES - Maaroufi, N; Rzeigui, J; Ayari, L; Abid, Z (European Scientific Journal, ESJ, 2015)
Burnout has been defined as a syndrome of emotional exhaustion, depersonalization and reduced personal accomplishment. Emergency services are the busiest and the most stressful units of hospitals. Aim: To assess the prevalence of burnout among Tunisian public hospital doctors and nurses and to determine its causes and perceived repercussions. Methods: in a first step, we assessed the work conditions, the perceived burn out and its possible consequences in 100 health care providers from two department of emergency of two hospitals: Tabarka and Jendouba from the North of Tunisia. In a second step, we used the Maslach Burn Inventory to assess the burnout symptoms in ours ample. Results: more than the half (56%) of ours ample had a burnout. 47% of the affected professionals had a high level of emotional distress, 36,6% had a high level of depersonalization and 33% had a low level of professional fulfillment . Burnout had a high level in nurse which affects three dimensions relative to physicians. A high level of burnout had found in health care provider which had sick leave with emotional distress (32%) (p=0,02), depersonalization(21%) and a low level of professional fulfillment (11%) . Conclusion: Our results corroborate partially with those of the literature and illustrate some parameters that can be the cause of burnout, such as working conditions, role ambiguity, and lack of experience among the young nurse. Therefore, it is important to take into consideration this various factors had their impact on quality of life of caregivers.